Thorsten Knauth/Rainer Möller/Annebelle Pithan (Hg.), Inklusive Religionspädagogik der Vielfalt. Konzeptionelle Grundlagen und didaktische Konkretionen. Münster/New York 2020 - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

Volker Leppin: Repräsentation und Reenactment. Spätmittelalterliche Frömmigkeit verstehen - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Bomb the System! Politische Pieces als Partizipationspraktik im öffentlichen Raum - Niemann, Sven (Kunst und Politik. Jahrbuch der Guernica-Gesellschaft. Schwerpunkt: Politisches Graffiti.)

IngridKG: A FAIR Knowledge Graph of Graffiti - Sherif, Mohamed Ahmed; da Silva, Ana Alexandra Morim; Pestryakova, Svetlana; Ahmed, Abdullah Fathi; Niemann, Sven; Ngomo, Axel-Cyrille Ngonga (Scientific Data)
Abstract Graffiti is an urban phenomenon that is increasingly attracting the interest of the sciences. To the best of our knowledge, no suitable data corpora are available for systematic research until now. The Information System Graffiti in Germany project ( Ingrid ) closes this gap by dealing with graffiti image collections that have been made available to the project for public use. Within Ingrid , the graffiti images are collected, digitized and annotated. With this work, we aim to support the rapid access to a comprehensive data source on Ingrid targeted especially by researchers. In particular, we present Ingrid KG, an RDF knowledge graph of annotated graffiti, abides by the Linked Data and FAIR principles. We weekly update Ingrid KG by augmenting the new annotated graffiti to our knowledge graph. Our generation pipeline applies RDF data conversion, link discovery and data fusion approaches to the original data. The current version of Ingrid KG contains 460,640,154 triples and is linked to 3 other knowledge graphs by over 200,000 links. In our use case studies, we demonstrate the usefulness of our knowledge graph for different applications.
Keywords: Library and Information Sciences; Statistics; Probability and Uncertainty; Computer Science Applications; Education; Information Systems; Statistics and Probability

A Pulsed Lidar System With Ultimate Quantum Range Accuracy - Kruse, Stephan; Serino, Laura; Folge, Patrick Fabian; Echeverria Oviedo, Dana; Bhattacharjee, Abhinandan; Stefszky, Michael; Scheytt, J. Christoph; Brecht, Benjamin; Silberhorn, Christine (IEEE Photonics Technology Letters)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

INGRID—Archiving Graffiti in Germany - Niemann, Sven (Document | Archive | Disseminate Graffiti-Scapes)

A parametrisation method for high-order phase reduction in coupled oscillator networks - von der Gracht, Sören; Nijholt, Eddie; Rink, Bob (arXiv:2306.03320)
We present a novel method for high-order phase reduction in networks of weakly coupled oscillators and, more generally, perturbations of reducible normally hyperbolic (quasi-)periodic tori. Our method works by computing an asymptotic expansion for an embedding of the perturbed invariant torus, as well as for the reduced phase dynamics in local coordinates. Both can be determined to arbitrary degrees of accuracy, and we show that the phase dynamics may directly be obtained in normal form. We apply the method to predict remote synchronisation in a chain of coupled Stuart-Landau oscillators.

Literature Reviews in Operations Research: A New Taxonomy and a Meta Review - Schryen, Guido; Sperling, Martina (Computers & Operations Research)

Prozesskettensimulation für das Clinchen mit beweglicher Matrize - Rossel, Moritz Sebastian; Meschut, Gerson (BLECHE+ROHRE+PROFILE)

RELD: A Knowledge Graph of Relation Extraction Datasets - Ali, Manzoor; Saleem, Muhammad; Moussallem, Diego; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille

UV-enhanced environmental charge compensation in near ambient pressure XPS - Arcos, Teresa de los; Müller, Hendrik; Weinberger, Christian; Grundmeier, Guido (Journal of Electron Spectroscopy and Related Phenomena)
In this work, we discuss the possibility of improving charge neutralization in near ambient pressure X-ray photoelectron spectroscopy by co-irradiating the sample with He I photons of 21.2 eV. This UV-enhanced neutralization of charges is a variation of the so-called environmental charge compensation, which uses the electrons produced by the photoionization of the ambient gas to neutralize the positive charges built at the sample surface. Adding an additional ionization source generates more charges at the sample but also larger amounts of electrons available for neutralization. The final surface charge equilibrium depends on different aspects of the experiment, such as the sample composition and geometry, the total ionization cross sections of the gas compared to the surface materials, the gas used, the luminosity and spot size of the sources used for photoionization, and the energy of the electrons present in the gas phase. Here we illustrate the efficiency of the UV-enhanced neutralization using three different dielectric samples with different geometries (a porous SiO2 monolith with an irregular surface, a flat mica sample, and a thin SiO2 film deposited onto a Si substrate), different X-ray spot sizes, and two different gases (N2 and Ar). The effect of biasing on the efficiency of the sample surface to attract electrons produced in the gas phase is also discussed.
Keywords: XPS; Near ambient pressure; Environmental charge compensation; UV

Entwicklung von Schülervorstellungen zu NOS & NOSI im Physikunterricht - Zwick, Linda; Webersen, Yvonne; Wodzinski, Rita (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

Erwerb und Messung fachdidaktischen Wissens zum Einsatz digitaler Medien - Große-Heilmann, Rike Isabel; Burde, Jan-Philipp; Riese, Josef; Schubatzky, Thomas; Weiler, David (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

Unterrichtsplanung mit sinnvoller Einbettung digitaler Medien im PU - Jordans, Melanie; Riese, Josef (Lernen, Lehren und Forschen in einer digital geprägten Welt Gesellschaft für Didaktik der Chemie und Physik Jahrestagung in Aachen 2022)

Local Protocols for Contracting and Expanding Robot Formation Problems - Castenow, Jannik

Online Algorithms for Allocating Heterogeneous Resources - Knollmann, Till

Efficient Modeling and Tailoring of Nonlinear Wavefronts in Dielectric Metasurfaces - Hähnel, David; Förstner, Jens; Myroshnychenko, Viktor (ACS Photonics)
Dielectric metasurfaces provide a unique platform for efficient harmonic generation and optical wavefront manipulation at the nanoscale. Tailoring phase and amplitude of a nonlinearly generated wave with a high emission efficiency using resonance-based metasurfaces is a challenging task that often requires state-of-the-art numerical methods. Here, we propose a simple yet effective approach combining a sampling method with a Monte Carlo approach to design the third-harmonic wavefront generated by all-dielectric metasurfaces composed of elliptical silicon nanodisks. Using this approach, we theoretically demonstrate the full nonlinear 2π phase control with a uniform and highest possible amplitude in the considered parameter space, allowing us to design metasurfaces operating as third harmonic beam deflectors capable of steering light into a desired direction with high emission efficiency. The TH beam deflection with a record calculated average conversion efficiency of 1.2 × 10–1 W–2 is achieved. We anticipate that the proposed approach will be widely applied as alternative to commonly used optimization algorithms with higher complexity and implementation effort for the design of metasurfaces with other holographic functionalities.
Keywords: tet_topic_meta

Gnaden-Gegenwart - Bach als Praktischer Theologe. Zum Amtsantritt des Thomaskantors vor 300 Jahren. Klaus Hock / Thomas Klie (Hg.): Bachzitate, Bielefeld 2021 - Ingo Bredenbach / Volker Leppin / Christoph Schwöbel (Hg.): Bach unter Theologen, Tübingen 2022 - Schroeter-Wittke, Harald (Praktische Theologie)

Outcomes-based contracting and public management reform: Lessons from a decade of experimentation - FitzGerald, Clare; Fraser, Alec; Kimmitt, Jonathan; Knoll, Lisa; Williams, James (International Public Management Journal)
Keywords: Public Administration; Business and International Management

Theoretical analysis of four-wave mixing on semiconductor quantum dot ensembles with quantum light - Rose, Hendrik; Grisard, S.; Trifonov, A. V.; Reichhardt, R.; Reichelt, Matthias; Bayer, M.; Akimov, I. A.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of an ensemble of semiconductor quantum dots is analyzed by wave-mixing processes, where we focus on four-wave mixing with two incident pulses. Wave-mixing experiments are often described with semiclassical models, where the light is modeled classically and the material quantum mechanically. Here, however, we use a fully quantized model, where the light is given by a quantum state of light. Quantum light involves more degrees of freedom than classical light as e.g., its photon statistics and quantum correlations, which is a promising resource for quantum devices, such as quantum memories. The light-matter interaction is treated with a Jaynes-Cummings type model and the quantum field is given by a single mode since the quantum dots are embedded in a microcavity. We present numerical simulations of the four-wave-mixing response of a homogeneous system for pulse sequences and find a significant dependence of the result on the photon statistics of the incident pulses. The model constitutes a problem with a large state space which arises from the frequency distribution of the transition energies of the inhomogeneously broadened quantum dot ensemble that is coupled with a quantum light mode. Here we approximate the dynamics by summing over individual quantum dot-microcavity systems. Photon echoes arising from the excitation with different quantum states of light are simulated and compared.